Three new gnathiid species with larvae ectoparasitic on coastal sharks from southwestern Japan (Crustacea: Isopoda) - Ota, Yuzo (Zootaxa, 2014)
Gnathiid larvae were collected from the gill chambers of coastal sharks in southwestern Japan. Some were reared in a laboratory aquarium and successfully metamorphosed into adults. Morphological observations of the adult males identified three undescribed species, which are designated Gnathia albipalpebrata n. sp., G. parvirostrata n. sp., and G. dejimagi n. sp. on the basis of their larval morphologies and pigmentation patterns.